2014
DOI: 10.1128/aac.00972-13
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Origin and Spread Route of Pyrimethamine-Resistant Plasmodium falciparum in Southern China

Abstract: bSoutheast Asia (the Thailand-Cambodia border) has been considered the primal epicenter for most antimalarial drug resistance; however, numerous molecular epidemiological studies have successively reported multiple independent origins of sulfadoxinepyrimethamine (SP) resistance-associated Plasmodium falciparum dhfr (pfdhfr) and pfdhps alleles in other areas. To better understand the origin and evolutionary pathway of the SP resistance in Southeast Asia, a total of 374 P. falciparum field isolates from the Yunn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…The quadruple mutant (C IRN I-S G KAA) was predominant, with a prevalence of 65.38% (Table 3 ), which is higher than reports from mainland EG (54%) [ 4 ]. The saturation of the Pfdhfr triple mutants could further induce the Pfdhps mutants, and thus, the presence of quadruple mutants (C IRN I-S G KAA) was common [ 40 ]. Although quintuple mutant genotypes (C IRN I-S GE AA) are highly linked to SP failure [ 34 ], this mutant was detected at a rate of 4.62% (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The quadruple mutant (C IRN I-S G KAA) was predominant, with a prevalence of 65.38% (Table 3 ), which is higher than reports from mainland EG (54%) [ 4 ]. The saturation of the Pfdhfr triple mutants could further induce the Pfdhps mutants, and thus, the presence of quadruple mutants (C IRN I-S G KAA) was common [ 40 ]. Although quintuple mutant genotypes (C IRN I-S GE AA) are highly linked to SP failure [ 34 ], this mutant was detected at a rate of 4.62% (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study locations, sample size (n), types of patient blood collected and years of collection were as follows: Hainan province (N = 136), with venous blood samples treated with EDTA from Sanya city (SY, n = 13) collected in 2005,2007; finger-prick blood spot samples collected on filter paper from Dongfang city (DF, n = 106) collected in 2004, 2007, and 2008; and Ledong county (LeD, n = 17) collected in 2004; and Yunnan province (N = 289), with finger-prick blood spot samples collected on filter paper from Dehong region (DH, n = 59) collected in 2007, venous blood samples treated with EDTA from Tengchong county (TC, n = 106) collected in 2006 and Lazan county (LZ, n = 71) collected in 2006, 2007; and blood smears from Xishuangbanna region (BN, n = 53) collected in 2006. Most samples (n = 349) were previously genotyped as part of a survey on pyrimethamine resistance in South China [ 27 ].
Figure 1 A schematic map showing the distribution of sampling sites for Plasmodium falciparum.
…”
Section: Methodsmentioning
confidence: 99%
“…In other studies, microsatellite markers were used to analyse the population genetics of P. falciparum samples collected from a single region or country, including Thailand [ 20 ], Philippines [ 21 ], Malaysian Borneo [ 22 ], Papua New Guinea [ 23 ], Western Kenya [ 24 , 25 ] and the Republic of the Congo [ 26 ]. In China, molecular biological studies on drug-resistant malaria were recently reported [ 27 , 28 ], although studies using neutral microsatellite markers to analyse the basic genetic diversity of the parasite are limited.…”
Section: Introductionmentioning
confidence: 99%
“…First, we did not detect pfCRT mutations from Malawi samples, consistent with the return of chloroquine-susceptible malaria in Malawi after chloroquine use was abandoned ( 41 ). The pfDHFR-pfDHPS mutant patterns IRNL -SG EG A and IRNL - A G E AA (mutations are underlined), which are linked to high-level sulfadoxine-pyrimethamine (SP) resistance ( 42 ), were observed as predominant alleles in Thailand and China samples, respectively. The pfMDR1 Y184F was the most common mutation observed in this study and has been reported as a common mutation found in Asia and Africa ( 43 45 ).…”
Section: Discussionmentioning
confidence: 99%